Termite nests as an abundant source of cultivable actinobacteria for biotechnological purposes - Nikhom Sujada (2018)
A total of 118 actinobacterial isolates were collected from the three types of termite nests (mound, carton, and subterranean nests) to evaluate their potential as a source of bioactive actinobacteria with antimicrobial activity. The highest number (67 isolates) and generic abundance (7 known genera) of actinobacterial isolates were obtained from carton nests. Streptomyces was the dominant genus in each type of termite nest. In the non-Streptomyces group, Nocardia was the dominant genus detected in mound and carton nests, while Pseudonocardia was the dominant genus in subterranean nests. A discovery trend of novel species ( < 99% similarity in the 16S rRNA gene sequence) was also observed in the termite nests examined. Each type of termite nest housed > 20% of bioactive actinobacteria that could inhibit the growth of at least one test organism, while 12 isolates, belonging to the genera Streptomyces, Amycolatopsis, Pseudonocardia, Micromonospora and Nocardia, exhibited distinct antimicrobial activities. Streptomyces sp. CMU-NKS-3 was the most distinct bioactive isolate. It was closely related to S. padanusMITKK-103 T , which was confirmed by 99% similarities in their 16S rRNA gene sequences. The highest level of extracellular antimicrobial substances was produced by the isolate CMU-NKS-3, which was grown in potato dextrose broth and exhibited a wide range (6.10×10 -4 -1.25 mg mL -1 ) of minimum inhibitory concentrations against diverse pathogens. We concluded that termite nests are an abundant source of bioactive strains of cultivable actinobacteria for future biotechnological needs.